The NIL Arms Race: Will the “Show-Me” State Come Out on Top? - Emma Eaton (Washington University Journal of Law and Policy, 2025)
Missouri’s name, image, and likeness (NIL) legislation positions the state as a leader in the evolving landscape of student-athlete compensation. Building on the momentum of NCAA v. Alston, Missouri’s law introduces innovative provisions, including allowing in-state, high school athletes to monetize their NIL, permitting the use of institutional intellectual property, and empowering coaches to facilitate NIL deals. These state reforms aim to attract talent and retain in-state athletes while also fostering economic growth. This Note argues that Missouri’s NIL policy sets a benchmark for other state schemes and offers a balance of deregulation and opportunity. Still, Missouri’s model depends on successfully navigating NCAA scrutiny, mitigating compliance risks, and adapting to the fluid regulatory environment in collegiate athletics. The Note concludes that Missouri’s proactive approach exemplifies the potential for states to shape the future of NIL in the absence of federal uniformity.
Keywords: NILReform; StudentAthleteRights; MissouriNILLaw